2022
DOI: 10.1038/s41598-022-10570-9
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the association between body mass index and blood pressure among 19-year-old men in Korea from 2003 to 2017

Abstract: The strength of association between the body mass index (BMI) and blood pressure (BP) varies with population and time. Therefore, identifying the trends in BMI-BP association in adolescents can help predict the upcoming metabolic and cardiovascular disease burden. For this reason, from physical examination data collected from 2003 to 2017, a total of 5,133,246 Korean men aged 19 years were assessed for the annual trends and changes in the BMI-BP association. During the 15-year period, the mean BMI increased fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
3
2
Order By: Relevance
“…In this repeated-measurement study, we calculated an annual mean increase in SBP of 0.98 mm Hg and an annual mean increase in DBP of 0.81 mm Hg for Pb workers from 2015 to 2017. One study from Korea pointed out that the annual mean increase in SBP was 0.22 mm Hg, and the annual mean increase in DBP was 0.24 mm Hg in the population of normal Korean men aged 19 years 39 . Their findings were much lower than those in our study, because the subjects in this study were occupational Pb workers, and theirs were the normal population.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…In this repeated-measurement study, we calculated an annual mean increase in SBP of 0.98 mm Hg and an annual mean increase in DBP of 0.81 mm Hg for Pb workers from 2015 to 2017. One study from Korea pointed out that the annual mean increase in SBP was 0.22 mm Hg, and the annual mean increase in DBP was 0.24 mm Hg in the population of normal Korean men aged 19 years 39 . Their findings were much lower than those in our study, because the subjects in this study were occupational Pb workers, and theirs were the normal population.…”
Section: Discussioncontrasting
confidence: 88%
“…One study from Korea pointed out that the annual mean increase in SBP was 0.22 mm Hg, and the annual mean increase in DBP was 0.24 mm Hg in the population of normal Korean men aged 19 years. 39 Their findings were much lower than those in our study, because the subjects in this study were occupational Pb workers, and theirs were the normal population. Another study from an occupational Pb exposure cohort concluded that a 10-μg/dL increase in blood Pb concentration was associated with a 0.9-mm Hg increase in SBP.…”
Section: Discussioncontrasting
confidence: 75%
“…Between 2003 and 2017, the prevalence of obesity among young adults increased from 16.7-21.4%. (Koh et al, 2022). Body mass index (BMI) tends to increase sharply during the transition from adolescence to adulthood and these increases have grown larger over time (Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…16 On the other hand, Koh et al mentioned in their paper that several studies have reported the inverse trend of increasing BMI with decreasing BP. 58 The capability of BMI to predict the risk of hypertension and CVD was doubted by few studies. 59.60 Though, we cannot ignore the fact that the underweight category also reported cases of SH (17.39%) and DH (26.96%).…”
Section: Discussionmentioning
confidence: 99%